The UK cellular microbiology network: Exploring the host‐bacterial interface. (17th July 2019) - Rohn, Jennifer L.; Mostowy, Serge; King, Jason S.; Unnikrishnan, Meera; Gutierrez, Maximiliano G.
Abstract: The UK Cellular Microbiology Network held its inaugural conference in February 2019. This stimulating day of scientific exchange will be the first of many, its organisers hope.